2022
DOI: 10.1093/jscr/rjac034
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous splenic mass with necrosis revealing an EBV-positive inflammatory follicular dendritic cell sarcoma

Abstract: Epstein–Barr virus-positive inflammatory follicular dendritic cell sarcoma is a variant of follicular dendritic cell neoplasm most often arising in the liver or spleen. Two histological patterns can be identified in this variant, namely a granulomatous and an eosinophil-rich one. We present the case of a 69-year-old woman with a splenic mass. After being removed, the mass was gray-whitish with an area of necrosis. Histology showed a diffuse distribution of epithelioid granulomas in a background of a dense lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In a Korean study [ 16 ], a large number of IgG4-positive plasma cells were found in six EBV-positive patients with IPT-like FDCS, suggesting that EBV has a key role in IPT-like FDCS. Three cases of IPT-like FDCS, characterized by IgG4 positivity, EBV positivity, and splenic involvement, were also reported in various studies [ 8 , 14 , 17 ]. Additional markers for FDCS encompass Ki-M4 and CD14 [ 35 ], CXCL13 and clusterin [ 36 ], gamma-synuclein and D2-40 [ 8 , 16 ], podoplanin and the low affinity NGFR [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In a Korean study [ 16 ], a large number of IgG4-positive plasma cells were found in six EBV-positive patients with IPT-like FDCS, suggesting that EBV has a key role in IPT-like FDCS. Three cases of IPT-like FDCS, characterized by IgG4 positivity, EBV positivity, and splenic involvement, were also reported in various studies [ 8 , 14 , 17 ]. Additional markers for FDCS encompass Ki-M4 and CD14 [ 35 ], CXCL13 and clusterin [ 36 ], gamma-synuclein and D2-40 [ 8 , 16 ], podoplanin and the low affinity NGFR [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 79%
“…We have reviewed the existing literature and discussed the disease in light of our findings. To date, there have been 29 published cases [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ] of splenic IPT-like FDCS, all of which have shown an association with EBV proliferation. Yet, the clinical presentation and pathological characteristics of this condition continue to be a subject of debate.…”
Section: Introductionmentioning
confidence: 99%